+0  
 
0
377
2
avatar+110 

What is the recursive rule for the sequence?
−7.4, −21.2, −35, −48.8, −62.6, ...
 
A) an = an+1 − 13.8, where a1 = −7.4
B) an = an−1 + 13.8, where a1 = −7.4

C) an = an+1 + 13.8, where a1 = −7.4

D) an = an−1 − 13.8, where a1 = −7.4

 Mar 14, 2018
 #1
avatar+17330 
+4

a1 is the first term = -7.4

the common difference between tems is  -13.8

 

the  an th  term is the previous term + the common difference, so

 

an = a(n-1) + (-13.8)   or     an= a(n-1) - 13.8       cheeky

 Mar 14, 2018
 #2
avatar+110 
+3

Thank you!

Jaleco  Mar 14, 2018

16 Online Users

avatar
avatar
avatar